Experimental study of the ocular behaviour in office workers as a visual comfort indicator in glare risk situations - Yamin Garretón, Julieta Alejandra (2014)
The daylight impact on the visual environment is fundamental on visual display terminal work (VDT). Visual performance and visual comfort should be considered for equal. The study (n=16) was performed at the experimental lighting laboratory. Office work with VDT was evaluated using STROOP task in two orientations: (with/without solar presence in the visual field). Our hypothesis states the existence of a relationship between ocular behavior and visual comfort of workers. An eye-tracker was employed in order to record the ocular gestural parameters: blinks, direction of gaze, eye aperture (Degree of eye?s openness) and pupil size, which were correlated with the vertical illuminance at the eye. Visual comfort was assessed with Glare Sensation Vote. Results indicate a strong negative linear correlation between eye illuminance and the degree of eye?s openness in the direct sunlight scenario (p=-0.636; s=0.008) and in diffuse light scenario (p=-0.661; s=0.005), that could be the main predictor of visual discomfort. This experiment allowed us to explore eye behavior patterns that could be visual comfort indices under glare risk situations.